Systematic Review of Hearing Preservation in Observed Vestibular Schwannoma - Reznitsky, Martin; Cayé-Thomasen, Per (Journal of Neurological Surgery Part B: Skull Base, 2019)
Objective This is a systematic review of the literature on the spontaneous course of hearing in patients observed with a vestibular schwannoma. Included studies are appraised using the Grading of Recommendations Assessment, Development and Evaluation system.Design PubMed, Embase, Medline, Cochrane library, and CINAHL (Cumulative Index to Nursing and Allied Health Literature) were searched for literature on hearing in patients observed with a vestibular schwannoma.Participants Of 217 evaluated papers, 15 were included, representing a total of 2,142 patients.Main Outcome Measures Hearing according to the AAO-HNS (American Academy of Otorhinolaryngology- Head and Neck Surgery) classification system. Weighted average of the proportion of patients preserving good hearing (>70% discrimination score and pure tone audiometry [PTA] < 30dB) and serviceable hearing (>50% discrimination score and PTA < 50dB) was determined.Results Fifty percent of patients presenting with good hearing at diagnosis had preserved this after a mean of 5 years of observation, whereas serviceable hearing was preserved in 54%. Patients with normal discrimination at diagnosis preserve their hearing very well. Very few studies exist on long-term hearing preservation.Conclusions After 5 years of observation, around half of patients will have preserved good or serviceable hearing. Patients with normal discrimination at diagnosis are more likely to preserve good hearing.
Keywords: systematic review; conservative treatment; wait-and-scan; hearing preservation; GRADE system